Dagstuhl ChoirSet: A Multitrack Dataset for MIR Research on Choral Singing - Rosenzweig, Sebastian; Cuesta, Helena; Weiß, Christof; Scherbaum, Frank; Gómez, Emilia; Müller, Meinard (Transactions of the International Society for Music Information Retrieval, 2020)
Choral singing is a central part of musical cultures across the world, yet many facets of this widespread form of polyphonic singing are still to be explored. Music information retrieval (MIR) research on choral singing benefits from multitrack recordings of the individual singing voices. However, there exist only few publicly available multitrack datasets on polyphonic singing. In this paper, we present Dagstuhl ChoirSet (DCS), a multitrack dataset of a cappella choral music designed to support MIR research on choral singing. The dataset includes recordings of an amateur vocal ensemble performing two choir pieces in full choir and quartet settings. The audio data was recorded during an MIR seminar at Schloss Dagstuhl using different close-up microphones to capture the individual singers’ voices. In this article, we give detailed insights into all stages of creating DCS: recording process, data preparation, generation of annotations as well as development of suitable interfaces for publicly accessing and reusing the data. Furthermore, we demonstrate the potential of the dataset for MIR research by discussing case studies on choral intonation assessment and multiple fundamental frequency (F0) estimation.<br
Keywords: Dagstuhl Choir; Set; Choral Music; Multitrack Recording; Choral Singing Analysis; F0